Representasi Kehilangan & Kesedihan Pada Puisi Bila Kau Tiada Karya Boy Candra: Sebuah Kajian Analisis Isi dan Gaya Bahasa - Dio Armando; Mohammad Naufal Mufid (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The poem ‘Bila Kau Tiada’ by Boy Candra is one of the most popular poetry works among readers. This poem raises the theme of loss and sadness experienced by a poet over the departure of a loved one. This article aims to analyse the poem ‘Bila Kau Tiada’ using content and stylistic analysis approaches. The content analysis will concentrate on the theme, meaning, and message conveyed in the poem, whereas the stylistic analysis will examine how the poet employs language to convey meaning and its impact on the reader.